Trace gas fluxes from managed grassland soil subject to multifactorial climate change manipulation - Deltedesco, Evi; Keiblinger, Katharina M.; Naynar, Maria; Piepho, Hans-Peter; Gorfer, Markus; Herndl, Markus; Bahn, Michael; Pötsch, Erich M.; Zechmeister-Boltenstern, Sophie (Applied soil ecology : a section of Agriculture, ecosystems & environment, 2019)
•A unique climate manipulation response surface approach was implemented.•Trace gas emissions from intact soil cores were examined by lab incubations.•CO2-fumigation resulted in non-linear treatment effects on lab CO2 emissions.•Field warming caused a linear increase in lab NOx emissions. Climate projections for the next decades expect a significant increase in air temperature and atmospheric CO2 concentration, particularly in Alpine grassland. Most past experiments focused on individual climate changes parameters, such as warming (eT) and increase in atmospheric CO2 (eCO2). There is still little knowledge about these environmental changes, their magnitudes, and interactions on soil trace gas emissions and temperature sensitivity of associated microbial processes. Therefore, we combined a multifactorial climate manipulation experiment with a laboratory incubation study. Intact soil cores were taken from the field site (“ClimGrass”) following two years of treatment. To assess not only the effects of individual climate change factors (elevated CO2 and elevated temperature) but also their combination on CO2, N2O, NOx, and NH3 a response surface model was applied after incubating soils in the lab. Also, temperature sensitivity of microbial processes involved in greenhouse gas production was determined. In general, we found no interactions among treatments. However, the response surface regression suggests that a maximum of CO2 emission occurred at the moderate CO2 treatment (+150 ppm) while extreme CO2 treatment (+300 ppm) showed similar CO2 emissions as the control. NOx emissions increased linearly with increasing temperature. Temperature sensitivity of associated microbial processes did not show a response to climate change treatments, likely due to a multitude of interacting soil and microbial processes. This study highlights the importance of considering not only the combination of climate manipulations but even different steps of CO2-enrichment and warming. We propose that more evident long-term trends are to be expected with sustained climate change manipulation treatments.